Cinematic echoes of covenants past and present : national identity in the historical films of Steven Spielberg and Andrzej Wajda - Garbowski, Christopher (2018)
The author analyzes selected historical films of Steven Spielberg and Andrzej Wajda with respect to historical memory and its impact on national identity. The Holocaust, self-scrutiny in historical memory, and foundation myths are focused in relation to the sense of covenant in the films drawn from the respective national communities.